Մայրական կաթից անջատված կաթնաթթվային բակտերիաների բնութագիրը - Լ. Վ. Դանիելյան (Հայաստանի ԳԱԱ)
В последние годы анализы микробного разнообразия грудного молока показали, что грудное молоко является источником живых молочнокислых бактерий, важных для формирования кишечной микрофлоры грудного ребенка. In recent years the analyses of microbial diversity of breast milk have shown that it is the source of alive lactic acid bacteria important for the formation of intestinal microflora of infant.
Keywords: Medicine; Therapeutics; Pharmacology